The Role of Adipose Tissue and Obesity in Causing Treatment Resistance of Acute Lymphoblastic Leukemia - Sheng, Xia; Mittelman, Steven D. (Frontiers in Pediatrics, 2014)
Obesity is responsible for ~90,000 cancer deaths per year, increasing cancer incidence and impairing its treatment. Obesity has also been shown to impact hematological malignancies, through as yet unknown mechanisms. Adipocytes are present in bone marrow and the microenvironments of many types of cancer, and have been found to promote cancer cell survival. In this review, we explore several ways in which obesity might cause leukemia treatment resistance. Obese patients may be at a treatment disadvantage due to altered pharmacokinetics of chemotherapy and dosage “capping” based on ideal body weight. The adipose tissue provides fuel to cancer cells in the form of amino acids and free fatty acids. Adipocytes have been shown to cause cancer cells to resist chemotherapy-induced apoptosis. In addition, obese adipose tissue is phenotypically altered, producing a milieu of pro-inflammatory adipokines and cytokines, some of which have been linked to cancer progression. Given the prevalence of obesity, understanding its role and adipose tissue in ALL treatment is necessary for evaluating current treatment regimen and revealing new therapeutic targets.